Spatial distribution of salinity, mud thickness and slope along mangrove ecosystem of the coast of Kupang District, East Nusa Tenggara, Indonesia - JERIELS MATATULA; ERNY POEDJIRAHAJOE; SATYAWAN PUDYATMOKO; RONGGO SADONO (Society for Indonesian Biodiversity, 2019)
Abstract. Matatula J, Poedjirahajoe E, Pudyatmoko S, Sadono R. 2019. Spatial distribution of salinity, mud thickness and slope along mangrove ecosystem of the coast of Kupang District, East Nusa Tenggara, Indonesia. Biodiversitas 20: 1624-1632. Mangrove ecosystem is suffering from continuous damage in terms of quality as well as quantity. Rapid mangrove conversion triggered by the ever-growing human population and activities have affected them adversely and caused mangrove deterioration in the coastal areas of Kupang District, Indonesia. The decline of quality and quantity of mangrove environment has caused highly alarming effects, such as an increase in abrasion, decrease of marine products, and sea-water intrusion. Although various efforts have been deployed for the rehabilitation of mangrove forests, there are no significant results yet. One of the reasons is such efforts are not based on scientific data on suitability of the physico-chemical conditions of the mangrove habitats. The objectives of this study was to analyse the physico-chemical conditions, such as salinity, mud thickness and slope of five selected mangrove locations, namely Tarus, Mata Air, Tanah Merah, Oebelo and Merdeka in Kupang District by systematic sampling method and to prepare spatial distribution maps for each of these parameters. Salinity conditions showed a wide variation in the study locations, starting from 10 ppm to 38.33 ppm. Mud thickness ranged from 20.11 cm to 84.77 cm in the entire study area. The highest mud thickness of 84.77 cm was found in Tanah Merah, followed by Oebelo with the maximum thickness of 74.66 cm, Mata Air with 56.22 cm, Merdeka with 53.66 cm, and the lowest mud thickness was in Tarus with 53.55 cm. Mangrove locations in Kupang District are dominated with 2-3% slope. The study indicated that the habitat conditions in the coastal area of Kupang District are suitable for the growth of mangroves. This study will also provide the basis to plan future mangrove rehabilitation programs in the study area.